Effect of supplementation of Purslane-Portulaca oleracea in hypercholesterolemic subjects - Tarkergari, S.; Waghray, K.; Gulla, S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Portulaca oleracea (Purslane) is a medicinal plant containing diverse phyto constituents grown all over the world. Several studies have reported its pharmacological effects like, antihypertensive, anti-inflammatory antioxidant, hypoglycemic, hypocholesterolemic, hypotriglyceridemia neuroprotective effects. Methods: Dried Portulaca oleraca leaves were incorporated into spice powder/ karampodi a south India food adjunct which was used for supplementation studies for 90 days (3 months) among hyper cholesterolemic subjects after obtaining a written informed consent. Biochemical parameters like lipid profile, i.e., total cholesterol, low density lipoprotein cholesterol, triglycerides, high density lipoprotein cholesterol, very low-density lipoprotein cholesterol, kidney function test, Liver function test were assessed. Baseline information, their medical history and 24hr dietary recall was elicited from the subjects through a pretested schedule. Results: The results have shown that the total cholesterol levels and its fractions along with triglycerides were significantly decreased, HDL-C increased significantly in the test groups from pre- supplementation to during-supplementation and were stable at post-supplementation period. Conclusions: Our results indicated that the spice powder was rich in polyunsaturated fatty acid had a strong hypo cholesterolemic and hypotriglyceridemic effect.